Correlation factor between standard surge waves for testing transient overvoltage suppressor devices (2008)
There is a varied number of standard impulse waves that are used to test the operation of transient surge suppressor devices. In particular, tests that check the maximum discharge pulse current are of importance. This paper analyzes the relationship between these different forms of impulsive waves, in order to obtain a correlation between them to apply one or the other with similar results. The conclusions reached from a simplified theoretical development are corroborated by laboratory measurement and simulation.